2022
DOI: 10.1051/bioconf/20224502009
|View full text |Cite
|
Sign up to set email alerts
|

Ligninolytic enzymes in Basidiomycetes and their application in xenobiotics degradation

Abstract: Variety of microorganisms have already proven their capabilities for degradation of wide range of wastes with anthropogenic nature. These pollutants, both liquid and solids, also include so called xenobiotics like phenol and its derivatives, PAHs, dyes, pesticides, pharmaceuticals, etc. Xenobiotics as bisphenol A (BPA), chlorhexidine (CHX), octenidine (OCT), other disinfectants and antiseptics have high ecotoxicological impact. Moreover, they can also impair our quality of life and our health interfering diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 166 publications
(262 reference statements)
0
5
0
Order By: Relevance
“…The white-rot fungi (Basidiomycota) pose a unique lignin-degrading enzymatic complex, which can break down complicated structures, such as extremely resistant to microbial attacks lignin, bisphenols, nonylphenols, synthetic dyes, etc. [10,13,16,17]. Different basidiomycete species are often used as model organisms for implementation in degradation processes.…”
Section: Resultsmentioning
confidence: 99%
“…The white-rot fungi (Basidiomycota) pose a unique lignin-degrading enzymatic complex, which can break down complicated structures, such as extremely resistant to microbial attacks lignin, bisphenols, nonylphenols, synthetic dyes, etc. [10,13,16,17]. Different basidiomycete species are often used as model organisms for implementation in degradation processes.…”
Section: Resultsmentioning
confidence: 99%
“…found that Gammaproteobacteria could respond indiscriminately to the exposure to environmental concentrations of soil pollutants, which is an indicator taxon for subsequent assessments of soil ecological risk. Brazkova et al (2022) found that Basidiomycetes produce lignin-degrading enzymes and reduce soil pollution. found that Chaetomium globosum CEF-082 and its metabolic ltrate could not only the growth of the plant but also reduce the incidence of soil-borne disease.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the antifungal activity may be due to more than one metabolite with different effects on the colonies and production times. White rot basidiomycetes (WRB) are a group of fungi that stand out to produce ligninolytic enzymes [46], in addition to a wide variety of structurally diverse bioactive metabolites [47], among which can be found antimycobacterial, antiviral, antifungals, immunomodulators, and anticancer, to name a few [48]. However, the study of the production of these metabolites, their cellular targets, and their application is limited compared to what has been explored for ascomycetes and bacteria.…”
Section: Production Kinetics Of Antifungal Activity In Cell-free Supe...mentioning
confidence: 99%